Implementation IMPLEMENTATION OF PERFORMANCE AUDIT BY THE REGIONAL INSPECTORATE AS AN INSTRUMENT FOR EVALUATION OF DEVELOPMENT PROGRAMS IN PUNCAK JAYA REGENCY, PAPUA - Kelina Yoman; Fedianty Augustinah; Aris Sunarya; Sarwani (Yayasan Nuraini Ibrahim Mandiri, 2025)
Performance audit is one of the important instruments in internal government supervision which plays a role in assessing the extent to which the effectiveness, efficiency, and economy of a regional development program can be achieved. This study aims to describe the implementation of performance audits by the Regional Inspectorate of Puncak Jaya Regency as an evaluation tool for the implementation of regional development programs. Using a descriptive qualitative approach with a case study method, this research was carried out in Puncak Jaya Regency, Central Papua, by involving the auditor of the Regional Inspectorate, the head of OPD, and the technical implementer of the program as the main informant. Data was collected through in-depth interviews, participatory observations, and documentation studies on performance audit reports and the realization of development programs from 2022 to 2023. The results of the study show that although the implementation of performance audits is not fully optimal, its function has made a real contribution in identifying structural and technical problems in development programs, such as inconsistencies in activity outputs, inefficiency in budget use, and weaknesses in reporting and internal control systems. Of the 12 OPDs audited, 47 findings were found that indicated the need to reformulate performance indicators, improve human resource competence, and improve the supervision system. However, the limited number of certified auditors, the unavailability of a digital audit system, and weak coordination across OPDs are still obstacles to the implementation of effective performance audits.This study recommends that the Regional Government of Puncak Jaya Regency strengthen the function of the Inspectorate through the development of technical regulations, capacity building of risk-based auditors, and strengthening an integrated supervision system. With a structured performance audit and supported by regional political commitments, it is hoped that development in the 3T region can be more measurable, accountable, and on target.